Analysis Of Independence In Children Aged 5–6 Years At PAUD Kasih Agape Kupang City - Mairda Yuventi Baksuni; Petrus Logo Radja; Retno J.K Lopo; Fredericksen Victoranto Amseke (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2026)
Background: Independence is a fundamental developmental competence in early childhood because it supports children’s self-care, decision-making, responsibility, and confidence. Despite its importance, many children aged 5–6 years continue to rely heavily on teachers and parents during daily learning activities, indicating that independence has not yet developed optimally. Objective: This study aimed to analyze the profile of independence among children aged 5–6 years by examining four dimensions of independence: self-care, simple decision-making, responsibility toward oneself and the environment, and self-confidence at PAUD Kasih Agape in Kupang City. Method: This study employed a descriptive qualitative approach. Data were collected through structured classroom observations, semi-structured in-depth interviews with two classroom teachers, and documentation of learning activities and children’s developmental records. The participants consisted of two teachers and five children aged 5–6 years selected through purposive sampling. Data were analyzed using the Miles and Huberman interactive model through data reduction, data display, verification, and conclusion drawing. The credibility of the findings was ensured through source and technique triangulation. Results: The findings revealed that children’s independence had not yet developed uniformly across the four dimensions. The strongest achievement was observed in simple decision-making, followed by responsibility, while self-care and self-confidence remained at the developing stage for most participants. Daily habituation practices, opportunities for autonomous participation, and positive teacher reinforcement contributed to the gradual development of children’s independence, although several children still required continuous teacher guidance and emotional support. Novelty: This study demonstrates that children’s independence develops through the interaction of structured habituation, child-centered learning, teacher scaffolding, and supportive social environments. Conclusion: Children’s independence can be strengthened through systematic habituation, meaningful opportunities for autonomous participation, consistent teacher scaffolding, and collaborative support between schools and families.